Soil Moisture Monitoring System Applied to the Internet of Things (IoT) Based Automatic Watering Equipment in Papaya Fields - Lola Adetia; Sri Wahyu Suciyati; Amir Supriyanto; Gurum Ahmad Pauzi (Journal of Energy, Material, and Instrumentation Technology, 2022)
In this research, the design of an automatic plant watering device and a real-time soil moisture monitoring system was realized in an internet of things (IoT) based papaya farm. The design of this automatic plant watering device aims to create an automatic plant watering system using the FC-28 sensor and a monitoring system using the Blynk application on papaya fields. In the system, the microcontroller used is an Arduino UNO with outputs, namely a dc pump, 16X2 LCD, and Blynk application. Based on the android interface app, the Blynk app can monitor the soil moisture value in real-time every 1 second. Data collection was done by measuring the moisture value in 3 papaya farms with different crop ages, and the tool will water when the soil moisture value read by the sensor is> 350 or <65%. Based on the study results, the device can run well, as shown by the pump can water when the soil moisture value is> 350 or <65 %, and the pump will stop when the soil moisture value is <350 or> 65%.